Repeatability of strain magnitude and strain rate measurements in the periodontal ligament using fibre Bragg gratings: An ex vivo study in a swine model. (21st March 2017) - Romanyk, Dan L.; Guan, Raymond; Major, Paul W.; Dennison, Christopher R.
Abstract: Measurement of periodontal ligament (PDL) strain in an ex vivo or in vivo setting of a complete tooth-PDL-bone complex (TPBC) has yet to be achieved in the literature. The objective of this study was to investigate inter- and intra-TPBC PDL strain measurement using fibre Bragg grating (FBG) strain sensors. Second and third premolars from the left and the right side of four swine mandibles were removed to yield sixteen TPBC samples. Samples were secured in a miniature load-frame equipped with a digital actuator used to apply apical-directed displacement to the tooth. The same tooth on left and right sides of the mouth were exposed to the same loading condition over ten trials allowing for comparisons in a split-mouth study. Displacements of 0.2 and 0.3 mm were considered along with displacement rates of 0.025, 0.05, and 0.1 mm/s, yielding six loading combinations. Hypothesis testing between left and right teeth revealed FBGs did not always measure the same strain between left and right TPBCs. For all strain measures, the average coefficient of variation (CV) (all data collected) was 2.16 (range: 0.274–10.71). For repeated measures in single TPBCs, the minimum CV ranged from 0.037 to 0.449, and generally coincided with the time of maximum strain measured over the test duration. Based on the findings of this study, it is suggested that FBGs can provide repeatable ex vivo strain measures in the PDL of complete TPBCs.